1972
DOI: 10.1111/j.1365-3180.1972.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF GROWTH REGULATORS ON CYNODON DACTYLON (L.) PERS., SORGHUM HALEPENSE (L.) PERS, AND CYPERUS ROTUNDUS L.*

Abstract: Summary. Plants of Cynodon dactylon (L.) Pers., Sorghum helepense (L.) Pers. and Cyperus rotundus L. were treated with the following growth regulators by dipping or foliar spraying: chlormequat, N‐dimethylamino succinamic acid (B–995), MH, 2‐chloroethane phosphonic acid (ethephon), flurecol and chlorflurecol. Effects varied from stimulation to inhibition of aerial growth, increases in shoot number, and kill of plants. The effect of combinations of foliar spraying with ethephon, MH, flurecol or chlorflurecol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Daylength does not affect tuberization dra matically in purple nutsedge as it does in yellow nutsedge (16,22,62,63). Horowitz (23) found natural daylength had no effect on tuberization in purple nutsedge and suggested that a minimum temperature of 20 C was necessary to stimulate the process.…”
Section: Tuber Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Daylength does not affect tuberization dra matically in purple nutsedge as it does in yellow nutsedge (16,22,62,63). Horowitz (23) found natural daylength had no effect on tuberization in purple nutsedge and suggested that a minimum temperature of 20 C was necessary to stimulate the process.…”
Section: Tuber Biologymentioning
confidence: 99%
“…Their rela tively short growth habit usually relegates them to the shade. Both yellow and purple nutsedge grow best under high soil moisture, high fertility (6,33), and high temperatures (9,22,65); those are conditions enhanced by growers to produce crops.…”
Section: Whole Plant Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Daminozide (B-9) appeared consistently to reduce tuber number and increased tuber germination substantially. The related B-995 had very little effect on nutgrass in trials reported by Horowitz (1972a). He also reported that the morphactins were of limited effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…), planta daninha perene, do grupo C 4 , com reprodução sexuada e vegetativa, é comum em países de clima tropical onde constitui problema sério em áreas agrícolas e industriais (HOROWITZ, 1972). A reprodução vegetativa é a mais importante forma de disseminação, pois tais estruturas são de fácil estabelecimento e de difícil controle, enquanto as sementes são produzidas esparsamente e sua germinação e emergência são baixas (SATORRE et al, 1996).…”
Section: Introductionunclassified